Investasi Penangkapan Ikan Tuna Semi Modern oleh PT Serena Marine di Perairan Sulawesi Utara - John E.H.J. Foeh; Reyner Tekad Tuera (Institut Pertanian Bogor, 2014)
Fish as a natural resource has a very high potential as a source of foreign exchange and income. Arrest of the proper techniques of some fish species will provide optimal benefits. The objective of this study is to analyze the financial feasibility of tuna fishing of PT Serena Marine in area of North Sulawesi Sea. Through certain assumptions and calculations of financial feasibility with present value concept (NPV, BCR and IRR) and profitability ratios such as ROA, ROI and ROE, also break-even point, and payback period. The result showed that, this business activity will be feasible and profitable. The results show that based on those profitability indicators were above 1%, NPV calculated is positive, BCR is 1.62 or > 1 while IRR is 46 % and greater than discounted interest rate using in this financial analysis, Payback period will be achieved on the year 25thmonths or after 2 years of operations. It shows the activity of tuna fishing by PT Serena Marine, is feasible in financial aspect.